Analisis Komitmen Organisasi dan Kompensasi Terhadap Produktivitas Kerja : Survei pada PT Ideal Sarana Cahaya Sukabumi - Andini Nidia Putri; R. Deni Muhammad Danial; Faizal Mulia Z (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine organizational commitment and compensation on the work productivity of PT employees. Ideal Sukabumi Light Facility. This research uses associative descriptive research methods with a quantitative approach. The sampling technique uses a saturated sampling technique, namely the entire population is sampled, so that there are 74 PT employees. Ideal Sarana Cahaya Sukabumi was used as a respondent. The data analysis techniques used are validity, reliability, then classical assumption tests, multiple correlation coefficients, correlation coefficients of determination, multiple linear regression, and hypothesis testing consisting of simultaneous hypothesis testing (F test) and partial hypothesis testing (T test). The results of this research are, the F test shows that organizational commitment and compensation together have a significant effect on work productivity with an F value of 18,948 > F table 3,126. Then, the T test results of organizational commitment on work productivity with a calculated T value of 2,269 > T table 1,993 show that organizational commitment has an effect on work productivity, and the results of the compensation T test on work productivity with a calculated T value of 3,309 > T table 1,993 show that there is an influence from compensation to work productivity